Optimization Design Method of Offset Slider Crank Mechanism based on the Optimum Transmission Force Performance - Ye Jinhu (Jixie chuandong)
According to the transmission efficiency of offset slider crank mechanism,based on the analysis of offset slider crank mechanism working stroke,the sum of unit invalid force in the working stroke is put forward to evaluate the mechanism transmission performance. The offset slider crank mechanism transmission angle function is derived,and the explicit analytical function equation for the sum of unit invalid force（ the symbol is） in the slow working-stroke is derived too. Combining with W function image and the W function characteristic is analyzed. Taking the slider crank mechanism of silver electrolytic cell for example,a detailed method of using W function in Matlab to optimize the design of the mechanism is stated.